Acupotomy for Osteoarthritis of the Knee; A Systematic Review and Meta-Analysis - Seung Min Lee; Cham Kyul Lee; Kyung Ho Kim; Eun Jung Kim; Chan Yung Jung; Byung-Kwan Seo; Bon Hyuk Goo; Yong Hyeon Baek; Eun Yong Lee (MEDrang Inc., 2021)
The purpose of this study was to evaluate the effectiveness and safety of acupotomy for the treatment of patients with knee osteoarthritis. There were 9 databases searched to retrieve randomized controlled trials until August 3, 2019 regarding acupotomy versus conventional Western medicine, conventional Western medicine treatment with and without acupotomy, and Korean medicine treatment with and without acupotomy, and meta-analysis was performed. Of 303 potentially relevant studies retrieved, 43 were systematically reviewed. All studies were conducted in China. Effective rate, visual analogue scale, and Western Ontario and McMaster Universities Osteoarthritis index were used as the evaluation scales. The Ashi point was selected most frequently. In all studies, the intervention group was more effective than the control group. Meta-analysis revealed that acupotomy showed statistically significant beneficial results. Although acupotomy had a beneficial effect on knee osteoarthritis, the risk of bias of the included studies was not low. The majority of the results from the evaluation scales used were highly heterogeneous (> 50%) which reduced confidence in the estimation of effect, or had a small sample size. Further clinical research and development is required in the future.